UAV helicopter relative state estimation for autonomous landing on moving platforms in a GPS-denied scenario. Issue 9 (2015) - Alarcon, Francisco; Santamaria, Daniel; Viguria, Antidio
Abstract: The objective of this work is to describe an innovative relative position and velocity state estimation approach for rotatory wing UAV linked with a rope. An autonomous landing of a UAV helicopter in a static and in mobile platform in absence of GPS are presented as application of this technology. The relative estimation is obtained using a device that provides rope orientation, and tension information, an altimeter and an IMU. All this information is combined using a sensor fusion strategy.